Ta’zir Punishment and Delegated Authority in Accordance with Islamic Jurisprudence and Afghanistan’s Enacted Laws - Rahimzai, Hisamudin; Mushfiq, Naqibulla (Integrated Journal for Research in Arts and Humanities, 2023)
Ta’zir punishment is the punishment of acts that do not have certain legal penalties, whether it is violating the rights of Allah (SWT), the rights of others, or the public interest. The legal basis of Ta’zir punishment is from the Holy Qur’an, the Prophetic Hadiths, the consensus of the Muslim community, and personal reasoning. In Islamic Sharia, there are many types of Ta’zir punishments, which range from advice up to execution, in consideration of the public order and interests of the community. In Ta’zir punishments, the determination of a sentence for the offender is subject to the authority and ability of the judge, and is specified in consideration of the interests and support of the community, along with the circumstances of the offense, the corrective effect of the sentence, and the character and criminal record of the offender. Many philosophies to legitimize disciplinary punishments, such as protecting humanity’s life and interests, reducing the magnitude of crime in society, and the correction and punishment of offenders are also incorporated. Ta’zir punishment has some unique characteristics, which include the indefiniteness of penalties, whereby the lawmaker’s authority and ability to punish is delegated to judges. Not only may the judge forgive the offender, but the personality and criminal record of the offender are also considered in determining the punishment. Because many people in Afghan society do not understand the concept of Ta’zir punishment, how they are applied, and how they are specified, so this Article is designed to help resolve these issues.